2005
DOI: 10.1126/science.1109411
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Vibrations That Destabilize Crystals and Characterize the Glassy State

Abstract: High-resolution inelastic neutron scattering was used to identify major sources of low-frequency vibrations in zeolite crystals. Dispersed and nondispersed modes were found, both of which are prominent in the early stages of compressive amorphization but decline dramatically in strength once a glass of conventional density is created. By identifying the dispersed modes with the characteristic vibrations of the various secondary building units of zeolitic structures, the Boson peak, a characteristic of the glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
118
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(131 citation statements)
references
References 26 publications
11
118
1
1
Order By: Relevance
“…For instance, the comparison of densified silica glass and α-cristobalite . Although this opposite trend is rare, it was observed, e.g., for amorphous and crystalline zeolite [27,28].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, the comparison of densified silica glass and α-cristobalite . Although this opposite trend is rare, it was observed, e.g., for amorphous and crystalline zeolite [27,28].…”
mentioning
confidence: 95%
“…A check of the densities of the various SiO 2 polymorphs (Table 1) [27,28]). A different density is accompanied by different sound velocity [29], which determines different properties of the elastic medium of the glass and influences its atomic dynamics [20,30,31].…”
mentioning
confidence: 99%
“…At the GT, because only 2D closed cycle-flow (that will generate a non-integrable phase  and an additional z-axial induced energy) corresponds to the abnormal heat capacity and boson peak [3,[7][8][9], we need only discuss all the IE loopflows on reference 0 (particle local) filed. The discussion further simplify to only consider the loop-flows formed by several consecutive arrows on a 2D projection plane, see Figures 2-5, and each arrow denotes an IE that has the same IE energy a   for flexible chain system.…”
Section: -Particle Cooperative Excited Fieldmentioning
confidence: 99%
“…Importantly, recent studies revealed that ZIFs may experience pressure-or temperature-induced amorphization [18]. Amorphization phenomena are better understood in inorganic zeolites, where low-energy vibrations that resonate at terahertz (THz) frequencies could destabilize porous crystals, causing structural instability and collapse [19].…”
mentioning
confidence: 99%